2004
DOI: 10.1007/s00464-003-9108-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic Nissen?Rossetti fundoplication in children with gastroesophageal reflux disease and supraesophageal symptoms

Abstract: Children with difficult-to-treat chronic respiratory symptoms must be evaluated for GERD, even if the need for surgery is low (8%), because complete eradication of reflux is mandatory. Radical treatment of GERD allows the pulmonologist to perform correct respiratory treatment and to prevent the development chronic and life-threatening complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…[10][11][12][13][14] However, our results have not shown that the outcomes of handicapped children who undergo laparoscopic fundoplication are satisfactory in terms of respiratory symptoms. Mattioli et al 15 recently reported excellent outcomes after laparoscopic fundoplication for GER disease in neurologically normal children with difficult-to-treat chronic respiratory symptoms. In contrast, Bui et al 16 reported findings similar to ours, that gastrostomy with fundoplication reduced the likelihood of aspiration pneumonia but that it still occurred in a significant number of handicapped children.…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12][13][14] However, our results have not shown that the outcomes of handicapped children who undergo laparoscopic fundoplication are satisfactory in terms of respiratory symptoms. Mattioli et al 15 recently reported excellent outcomes after laparoscopic fundoplication for GER disease in neurologically normal children with difficult-to-treat chronic respiratory symptoms. In contrast, Bui et al 16 reported findings similar to ours, that gastrostomy with fundoplication reduced the likelihood of aspiration pneumonia but that it still occurred in a significant number of handicapped children.…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of laparoscopic fundoplication for children with respiratory problems secondary to GERD has been observed by several groups [14][15][16][17]. Mattioli et al [16] reviewed their outcomes after laparoscopic fundoplication (Nissen-Rossetti) in children with preoperative supraesophageal symptoms (mainly respiratory) of GERD and demonstrated complete resolution of pulmonary symptoms in more than two thirds of patients with decreased symptoms or medication use in another 27% of patients.…”
Section: Laparoscopic Vs Open Fundoplication For Gerdmentioning
confidence: 96%
“…Mattioli et al [16] reviewed their outcomes after laparoscopic fundoplication (Nissen-Rossetti) in children with preoperative supraesophageal symptoms (mainly respiratory) of GERD and demonstrated complete resolution of pulmonary symptoms in more than two thirds of patients with decreased symptoms or medication use in another 27% of patients. In another report, they demonstrated that carbon dioxide insufflation did not impair cardiovascular function during the laparoscopic procedure if the intraabdominal pressure was maintained at lower than 10 mm Hg [15].…”
Section: Laparoscopic Vs Open Fundoplication For Gerdmentioning
confidence: 98%
“…The bronchoalveolar lavage helps assess for the presence of neutrophils and lipid-laden macrophages in the aspirate, which would be consistent with aspiration from reflux. 12 …”
Section: Diagnosis and Work-upmentioning
confidence: 97%